A note on the predatory hybotid fly genus Crossopalpus found at the Kerkini National Park in Greece with an illustrated key to the species occurring and expected in Greece - Grootaert, Patrick; L. T. Beuk, Paul (ENTOMOLOGIA HELLENICA, 2024)
Six species of the genus Crossopalpus were collected during a recent survey in the Kerkini National Park in northern Greece. Three species are reported from Greece for the first time: Crossopalpus chvalai Kovalev, 1976, Crossopalpus flexuosus (Loew, 1840) and Crossopalpus humilis (Frey, 1913). A key is provided to the species occurring in Greece as well as those expected to occur in Greece. New illustrations of the male genitalia of all these species are given.